2014
DOI: 10.1590/s1677-5538.ibju.2014.06.19
|View full text |Cite
|
Sign up to set email alerts
|

Extra corporeal shockwave lithotripsy resulting in skin burns – a report of two cases

Abstract: ARTICLE INFO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…When an extracorporeal device is used to distribute the incident energy over a large skin area, the device has a wide aperture and long focal length to decrease the acoustic intensity at the wave site to avoid skin burn. However, severe full skin burns following extracorporeal shock wave lithotripsy (ESWL) for renal calculi [18] or second-degree burns after shock wave lithotripsy [19] have been reported. Also, some patients face post-procedure side effects, such as pain, vomiting, and wounds on their skin.…”
Section: Limitations and Complicationsmentioning
confidence: 99%
“…When an extracorporeal device is used to distribute the incident energy over a large skin area, the device has a wide aperture and long focal length to decrease the acoustic intensity at the wave site to avoid skin burn. However, severe full skin burns following extracorporeal shock wave lithotripsy (ESWL) for renal calculi [18] or second-degree burns after shock wave lithotripsy [19] have been reported. Also, some patients face post-procedure side effects, such as pain, vomiting, and wounds on their skin.…”
Section: Limitations and Complicationsmentioning
confidence: 99%
“…In lithotripsy, cavitation is more likely to create injury within blood vessels and to cause mechanical damage to organs such as the kidney. However, severe full skin burns after extracorporeal shock wave lithotripsy for renal calculi (Rao et al 2014) or seconddegree burns after shock wave lithotripsy (Rangarajan et al 2012) are often reported. Some patients also face post-operative side effects such as pain, vomiting and skin wounds.…”
Section: Urinary Tract Systemmentioning
confidence: 99%